Water Monitoring System Using Remote-Control Boat - Mohamed Aslam, Mohamed Shazwan; Hasliza Hassan, (Progress in Engineering Application and Technology, 2025)
Water is an indispensable resource in the food industry, fundamental to various processes such as ingredient mixing, cleaning, and cooling. Ensuring the quality of this water is paramount for upholding food safety standards and adhering to regulatory requirements. Conventional methods of water quality monitoring, which typically involve manual sampling and laboratory analysis, are often laborious, time-consuming, and only offer a static snapshot of water conditions. These limitations become particularly challenging when monitoring large water bodies like reservoirs and treatment tanks, where comprehensive coverage is difficult to achieve. The lack of automation and real-time feedback in existing systems can lead to delayed detection of contaminants,resulting in costly recalls, regulatory penalties, and damage to a company's reputation, especially in an industry where minor contamination can have severe consequences, such as foodborne illnesses. This project addresses these critical challenges by proposing a remote-controlled (RC) boat-based water quality monitoring system integrated with Internet of Things (IoT) technology. The system utilizes a combination of turbidity, Total Dissolved Solids (TDS), and temperature sensors to measure key water quality parameters, transmitting real-time data to a mobile application for remote oversight. The RC boat facilitates data collection from multiple points within a water body, significantly improving monitoring coverage and accuracy compared to static sensors. This innovative solution seeks to enhance water monitoring efficiency in the food industry, mitigate contamination risks, and ensure compliance with food safety regulations.